Evaluación de la contaminación sonora en la ciudad de Morales, distrito de Morales, provincia de San Martín - Reátegui Pereyra, Engell Boris (2012)
The Sonorous or Acoustic Pollution is one of the environmental problems more transcendentes in the cities, with the present work of investigation named Evaluation of the Sonorous Pollution in the City of Morales, District of Morales, Province of St Martín, Region St Martín, it developed with the aim to evaluate the sonorous pollution in the principal streets caused by the traffic and the Discotheques in the city of Morales, 2012. The type of investigation is descriptive, there has been chosen a total of eight points of evaluation in the city of Morales and from 6.30 to 7.30 have taken the information with a sound level meter of property of the Municipality District of Morales, in three shifts, the first shift am, the second shift of 12.0 m to 1.00 pm, and the third shift from 5.30 to 6.30 pm. We have managed to calculate the quantity of vehicles that circulate along the principal streets of the city, classified under motorcycles, Trimovil and major vehicles. In other words, the present work of investigation tries to know and put in knowledge the scope ofthe acoustic pollution on the population ofthis city. The final conclusion is that the sonorous pollution in the city of Mulberry trees is caused by the quantity of vehicles that circulate, principally for those that have opened his pipes of leak and for sorne night centers, this will serve to the Municipality District of Morales and his civil servants to realize actions and effective measures to control and to mitigate this pollution. On the other hand it is important to mention that to improve the evaluation of the sonorous pollution is necessary the development of another complementary thesis that it helps to evaluate better to the night centers in the city. What we claim is to collaborate and to help to mitigate the sonorous current pollution. By means of the formless present we will announce the results of the investigation, illustrated with information of the evaluation, graphs, information of quantity of vehicles, results of sound level meter and recommendations to level of integral management and punctual actions to realize by the Municipality to complement this study and to control the air pollution. Key words: Sonorous or Acoustic Pollution.